Novel human astroviruses in pediatric respiratory samples: A one‐year survey in a Swiss tertiary care hospital. Issue 11 (16th July 2018) - Cordey, Samuel; Zanella, Marie‐Celine; Wagner, Noemie; Turin, Lara; Kaiser, Laurent
Abstract : Although classical human astroviruses (HAstV) are known to be a leading cause of viral gastroenteritis, the pathogenesis and clinical manifestations of novel HAstV remain largely unknown. There is mounting evidence that, in contrast to classical astroviruses, novel HAstV exhibit tropism for the upper respiratory tract. This one‐year period prevalence screened all available clinical nasopharyngeal swab samples collected from pediatric patients aged ≤5 years for novel and classical HAstV using real‐time reverse transcription polymerase chain reaction. A total of 205 samples were tested; two novel HAstV cases were detected for a prevalence of 1.3%, with viral loads suggesting active upper respiratory tract replication. No classical HAstV was detected.